THE MUCO-GINGIVAL-PERIODONTAL EFFECTS AFTER THE ADMINISTRATION OF CERTAIN DRUGS PRESCRIBED IN THE TREATMENT OF SYSTEMIC DISEASES. REVIEW - Liliana Pasarin; Irina Georgeta Sufaru; Alexandra Martu; Cristala Diana Nitescu-Kappenberg; Diana Anton; Raluca Mocanu; Georgiana Laza-Demirbuken; Sorina Mihaela Solomon (Romanian Dental Association for Education, 2019)
Certain drugs may cause periodontal tissue changes and may influence the progression of periodontal disease with clinically obvious manifestations. The widespread use of drugs for both therapeutic indications in some systemic diseases and for recreational effects, can generate very important effects and implications for the presence and characteristics of periodontal disease in certain individuals and may be an important aspect in considering personalized medication in the field of periodontology. These aspects are more evident in the elderly, poly-medicated patients, characterized by long-term use of the large-scale therapeutic medication known as "polypharmacy", which has been reported in more than 30% of people.